TUBEIMOSIDE-1, A TRITERPENOID SAPONIN: AN UPDATE ON ITS PHARMACOLOGICAL EFFECTS - SOROMOU, LANAN WASSY; FODÉ CAMARA, MAMADOU (Asian Journal of Pharmaceutical and Clinical Research, 2022)
It is known that humans have been using natural products for medicinal use for ages. Tubeimoside-1 (TBMS1) is a triterpenoid saponin first isolated in China from Bolbostemma paniculatum (Maxim) Franquet, Cucurbitaceae. This review provides a deep overview on TBMS1 and extensively summarizes its pharmacological functions. As result, TBMS1 has drawn great interest in medicinal field due to its multiple pharmacological functions such as anticancer, anti-inflammatory, antitumor, antidiabetic, anti-human immunodeficiency viruses, and neuroprotective properties. Further, TBMS1 plays an important role in a wide range of pharmacological processes. Although possessing important functions, further experimentations are required to broaden the scope of its application.